Introducing Public Participation Methods into the Pedagogical Process - Pavlakovič Farrell, Barbara; Koščak, Marko (University of Maribor Press, 2025)
The textbook "Introducing Public Participation Methods into the Pedagogical Process" highlights the importance of the involvement of different communities in processes for planning tourism development. In the introductory part, the concept of public participation in tourism planning processes is presented. The reasons for and levels of public involvement in development processes are explained. The textbook also presents examples of good practices in cooperation with the local community from Slovenia and abroad. The textbook then focuses on the public involvement process itself, where the individual stages of participation are described. Next, concrete advice is given regarding the organisation of events where the public are involved. In particular, public participation techniques, which can be used in cooperation with various stakeholders, are highlighted. At the end, the textbook presents examples of the inclusion of local participation in the study process at the Faculty of Tourism of the University of Maribor. It provides a draft work plan for future examples of including cooperation with communities in the study process.